The Katipunan and the revolution : memoirs of a general with the original Tagalog text - Alvarez, Santiago V.; Malay, Paula Carolina S.; Paredes, Ruby R. (Quezon City : ADMU Press; [S.I.]: Center for Southeast Asia Studies, University of Wisconsin-Madison, 1992)
English and Filipino Text
Keywords: Philippines -- History -- Insurrection, 1896-1898; Alvarez, Santiago V